2013
DOI: 10.1002/rcs.1500
|View full text |Cite
|
Sign up to set email alerts
|

Robotic‐assisted hepatic resection: a systematic review

Abstract: Our systematic review suggests robotic-assisted hepatic resection is safe and feasible, with low mortality and morbidity rates. Further research is needed to determine if oncological outcomes are similar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 15 publications
(51 reference statements)
1
19
0
Order By: Relevance
“…(33,34) Most of the published studies involved a small retrospective series of patients, and demonstrated that robotic hepatectomy is safe and feasible when performed by experienced surgeons. (31,34,35) Nonetheless, there is evidence to suggest that robotic hepatectomy may be superior to conventional laparoscopy. For instance, a study by Tsung et al demonstrated that patients who underwent robotic hepatectomy were less likely to require conversion to hand-assisted surgery as compared to those who underwent laparoscopic hepatectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(33,34) Most of the published studies involved a small retrospective series of patients, and demonstrated that robotic hepatectomy is safe and feasible when performed by experienced surgeons. (31,34,35) Nonetheless, there is evidence to suggest that robotic hepatectomy may be superior to conventional laparoscopy. For instance, a study by Tsung et al demonstrated that patients who underwent robotic hepatectomy were less likely to require conversion to hand-assisted surgery as compared to those who underwent laparoscopic hepatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…(36) Pelletier et al reported in their systematic review that robotic hepatectomy enabled intracorporeal suturing and tying in difficult locations, as well as efficient control and management of bleeding, such that the need for conversion to open surgery was reduced. (35) As with laparoscopic hepatectomy, most reported cases of robotic hepatectomy were performed in highly specialised tertiary referral centres. While most of the aforementioned studies reported promising short-term outcomes, the long-term oncological outcomes and cost-effectiveness of the procedure remain unanswered.…”
Section: Discussionmentioning
confidence: 99%
“…To sum up, although it has not been clearly shown whether RAL hepatic and pancreatic surgery are superior to the laparoscopic technique in selected patients, authors report that the robotic technique can be performed safely in hepatic and pancreatic surgery. More expert studies in this field are necessary to better evaluate the long term oncological results and cost analyses of RAL hepatic and pancreatic surgery (37 (4,41,42). In addition, laparoscopic surgery has been shown to offer better postoperative comfort to the patient.…”
Section: Robotic Hepatopancreaticobiliary System Surgerymentioning
confidence: 99%
“…The largest study including 41 patients reports excellent morbidity and mortality rates of 7% and 0%, respectively, as well as 2-year overall and disease-free survival rates of 94% and 74%, respectively [117] . Thus, technological progress also finds its way into liver surgery with promising first results and experiences [118] , providing more possibilities for further development and improvement of treatment options and thus the prognosis for our patients with HCC.…”
Section: Open Vs Laparoscopicmentioning
confidence: 99%